Turn in the South - Naipaul, V S (Picador, 2011)
Travelling from Atlanta to Charleston, from Tallahassee to Tuskegee, from Jackson to Nashville and Chapel Hill, Naipaul covers the South of the US and finds a culture which he describes as consisting of order, faith, music and melancholy, both defined and burdened by a desperate past.